The Status of Coconut Methyl Ester as an Alternative Fuel as Assessed by Motorists in Selected Cities in Laguna: Basis for Innovation - Ferranco , Minerva D. (International Journal of Aquatic Research and Environmental Studies, 2026)
This study evaluated the effectiveness of coconut methyl ester (CME) as an alternative fuel blended with diesel, as perceived by motorists in selected cities in Laguna. Effectiveness was assessed in terms of price, fuel consumption, health impact, engine performance, and smoke emission, while satisfaction was measured across tangibles, reliability, responsiveness, assurance, and price. Using a descriptive research design, data were gathered from 250 respondents composed of drivers, operators, and local government personnel through a validated questionnaire. Results indicate that CME-blended diesel is perceived as effective across all performance indicators, with no significant differences between respondent groups in most domains except health and smoke emission. Respondents also expressed overall satisfaction, although concerns were identified regarding service delivery, product awareness, and maintenance. The findings suggest that CME is a viable renewable fuel alternative, but public education, technical training, and regulatory support are essential to optimize its implementation. The Philippines currently mandates a nationwide 3% CME biodiesel blend in diesel fuel, reinforcing its national renewable energy strategy.